GEOCHEMICAL CHARACTERISTICS OF THE NEOARCHEAN (2800-2700 MA) TAISHAN GREENSTONE BELT, NORTH CHINA CRATON: EVIDENCE FOR PLUME-CRATON INTERACTION - Polat A.; Fryer B.; Gagnon J.; Zhang S.; Li J.; Kusky T. (My University, 2006)
The 2800-2700 Ma Taishan greenstone belt, North China Craton, consists of an association of komatiites, pillow basalts, banded iron formations, conglomerates, and greywacke sandstones. The belt was intruded by high-Al tonalite-trondhjemite-granodiorite (TTG) plutons and deformed under amphibolite-grade metamorphism at about 2700 Ma. At the bottom of the association komatiites are characterized by locally well-preserved spinifex, cumulate, and breccia textures. Spinifex komatiites have uniformly high-MgO (31-33 wt.%), but low-Al2O3 (2.8-5.7 wt.%), TiO2 (0.14-0.24 wt.%), and Zr (4.6-9.6 ppm) contents. Towards the top of the sequence komatiites become less magnesian (MgO = 22-23 wt.%), more aluminous (Al2O3 = 6.2-8.9 wt.%), and display higher concentrations of incompatible elements. Based on [Al2O3] versus [TiO2] molecular relations, these rocks plot mainly in the field of Al-depleted komatiites. Komatiites occurring at stratigraphically lower levels have concave-upward LREE patterns and negative Nb anomalies (Nb / Nb* = 0.19-0.96). Stratigraphically upper komatiites and pillow basalts also share the negative Nb anomalies. There are strong correlations between the initial εNd values and indices of crustal contamination and olivine fractionation, suggesting that the geochemical characteristics of the Taishan komatiites can be best explained by olivine fractionation and assimilation of 2-6% LREE-enriched older continental crust or sediments. Relict olivine grains in the Taishan komatiites have lower Mg-numbers (Fo79-84) than whole-rock (84-90) and serpentine-chlorite-amphibole matrix (90-95), indicating that whole-rock composition is not in equilibrium with olivine composition. This disequilibrium is likely have resulted from the enrichment of Fe in recrystallized olivines during amphibolite metamorphism at ~2700 Ma. Conglomerates are composed dominantly of gneissic, granitic, and amphibolitic clasts. Grain types and trace element characteristics of sandstones are consistent with a continental source area. There are zircon and apatite xenocrysts in the stratigraphically lower komatiites. Collectively, these geological features are consistent with the deposition of the greenstone belt on continental basement. Accordingly, we propose a geodynamic model of plume-craton interaction to explain the geological and geochemical characteristics of the Taishan greenstone belt. © 2005 Elsevier B.V. All rights reserved.
Keywords: ARCHEAN; GREENSTONE BELT; KOMATIITE; MANTLE PLUME; NORTH CHINA CRATON; Докембрий::Архей::Неоархейская; Precambrian::Archean::Neoarchean